EVALUASI KESESUAIAN LAHAN DAN ARAHAN PENGENDALIAN PEMANFAATAN RUANG DI KECAMATAN MANDAU - Wahyudi, Ade (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
Mandau Urban Area is a fast-growing economy which plays an important role as a center of trade and services as well as plantations, strategic industrial area on a national scale with oil and gas potential. Given these economic potentials, Mandau Urban Area undergoes significant physical development which causes high rate of land conversion and is being susceptible to manipulation of spatial utilization. As a result, spatial utilization in Mandau Urban Area is inconsistent with The Bengkalis Regency spatial plan. This research aims to evaluate the land suitability and the implementation of the instruments regarding spatial utilization monitoring. Also, it provides some recommendations concerning spatial utilization monitoring in order to ensure the orderly spatial utilization in Mandau Urban Area. In this study, development and evaluation methods are adopted. The result indicates that the instruments of spatial utilization monitoring in Mandau Urban Area has worked well. The percentage of land use, which is consistent with the spatial pattern defined in The Bengkalis Regency Spatial Plan, is approximately 79.9%. Moreover, the percentage of spatial pattern which has not been implemented yet reaches 8.3%; while the remaining percentage (3.3%) is inappropriate spatial pattern. Therefore, This study concludes some recommendations on spatial utilization monitoring.